M20 Finding the missing millions: case finding for COPD in people attending other long term condition clinics in primary care. (14th November 2013) - Halpin, DMG; Holmes, S; Calvert, J; McInerney, D
Abstract : Over 40% of people with COPD remain undiagnosed. Co-morbidities are common in people with COPD but COPD is also a comorbidity of other long term conditions. As SHA respiratory leads in the SW we used this fact to develop a pilot programme to case find people with COPD among patients attending other long term clinics in primary care. The project was developed by the Leads and partially supported by Astra Zeneca, Boehringer Ingelheim, Chiesi & Novartis who provided support for additional health care professional time, but it was also adopted by Bristol CCG. Practices were asked to show all current or ex-smokers aged ≥ 35 attending a long term condition clinic who were not known to have COPD a Patient Information Sheet and ask them to complete a questionnaire designed to help identify people with COPD (1). Patients were also asked to perform microspirometry using an ASMA-1 device, their age, height, & smoking status were recorded. If they scored highly on the questionnaire and had an FEV1 below the lower limit of normal (LLN), their MRC breathlessness and CAT scores were recorded and they were offered further assessment within the practice to confirm the diagnosis. Smokers were offered referral to cessation services. 573 patients (323 men) were seen in 11 practices between Sep 2012 & May 2013. Mean age 64.6 (range 36–90). 265 had high questionnaire scores and 115 of these also had FEV1 less than LLN–20% of all patients seen. The mean FEV1 (%pred) in these patients was 58.6 (range 5.5–77.6). 86 had an FEV 50–80% predicted, 25 30–50% predicted. 44 had an MRC score of 0, 13 of 1, 44 of 2, 8 of 3 and 4 of 5. The mean CAT score was 13.4 (range 2–40). 44 (38%) were still smoking and 17 of these accepted referral to cessation services. 27 of the other 125 smokers assessed but not thought to have COPD also accepted referral. Case finding using this method in people already attending primary care clinics has a high yield (1 in 5) takes little time and deserves wider adoption. References: Respiration 2006;73:285–95.